Seventh Periodic Monitoring Report on the Status of Implementation Plans in Response to Board-Endorsed IEO Recommendations. (Policy Papers; Policy Paper ;, 2015)
The Seventh PMR includes: (i) a discussion of progress made over the last year on the actions corresponding to four Management Implementation Plans (MIPs) that were classified as still 'in progress' in the previous PMR; and (ii) an assessment of the progress made in achieving the high-level objectives in three areas directly related to those MIPs. In addition, an update on substantive issues related to five older MIPs agreed since 2007 is provided at the end of the report. Three new evaluations have been completed by the IEO since March 2014. In July and August 2015, Management issued the MIPs in response to these evaluations. Given that only a short time has passed since their completion, progress in addressing the actions contemplated in those MIPs will be discussed in the next PMR.